Determinants of corporate hedging practice in Malaysia / Ahmad Akmal Sadiq Ahmad Suhaimi - Ahmad Suhaimi, Ahmad Akmal Sadiq (2021)
Risk management is formally defined as the process by which an organization assesses and addresses its risk. It helps an organization to identify, evaluate, analyse, monitor, and mitigate the risks that threaten the achievement of an organization's strategic objectives in a disciplined and systematic way. It has always been a matter of continuous concern to most corporations, especially, the changes in the exchange rate have been a major risk to firms involved in the imports and exports. Therefore, to minimize the risk associated, hedging can reduce underinvestment costs since it reduces the probability of financial distress by shielding future stream cash flow from the changes in the exchange rates. Choice of hedging instruments and determinants of derivatives hedging seems to reflect decision making of managers in developed countries as they tend to have less information asymmetry, efficient market for corporate control, better institutional and legal systems. Hence, this research intends to show the determinants of corporate hedging practice would be different outside developed countries, specifically, Malaysia due to different firm specific characteristics.